PENGARUH TINGGI MUKA AIR TANAH PADA POPULASI SERANGGA DI LAHAN RAWA GAMBUT DESA KUALA DUA KABUPATEN KUBU RAYA - Situmorang, Monica Evarina; Astiani, Dwi; Ekyastuti, Wiwik (Universitas Tanjungpura, 2019)
Insects are the most dominant group of animals living on the face of the earth and their role is ecologically significant. The purpose of the study was to observe the type of population and identify the effect ofÂ water level on the diversity of insect species found in the peat swamp area of Kuala Dua village. Data assesment was done by using survey method with systematic sampling. Observation plots was adjusted to the field conditions with water level 30, 40, 50 and 60 cm. The results showed that there were 15 insects species Â belonging to 8 orders from 11 different families. The most common insects found in various TMAs that were observed, were Neurothemis fluctuan from the Odonata order. Physical conditions of the environment greatly affect the life of insects, such as having many types of plants which became food Â for insects. It can be concluded that the level of diversity of insect species has a relationship with environmental conditions such as vegetation, pH, and water level.Keywords: Insect population, systematic sampling, water level